ANALISIS PENERAPAN KESELAMATAN RADIASI SINAR-X PADA PETUGAS RADIASI DI INSTALASI RADIOLOGI RUMAH SAKIT PEKANBARU MEDICAL CENTER (PMC) - Rennyta Monita; Zulmeliza Rasyid; Muhamadiah Muhamadiah; Firman Edigan; Masribut Masribut (STIKes Al-Insyirah Pekanbaru, 2020)
ABSTRACT Radiation safety is an action taken to protect patients, workers, public, and the environments from the radiation hazards. Given the large potential for radiation hazards in the use of X-rays, safety is an important factor so as to minimize the risk due to work in radiology installations and the impact of radiation on radiation workers. This type of research uses a qualitative descriptive method with observation data collection techniques, interviews, and documentation studies. There were 6 informants in this study including: one head of the radiology installation room, two radiographers, one radiation protection officer, one medical physicist, and one hospital OHS officer. The data validity test used source triangulation and technical triangulation techniques. The results of the analysis of this study indicate that the application of radiation safety has not been carried out as a whole, where there are aspects that do not meet BAPETEN regulatory standards such as not carrying out health monitoring according to regulatory provisions, lack of radiation protection training, lack of radiation protection equipment, absence of surveyors, incomplete records of activity implementation and absence of potential exposure tests. The recommended recommendations are to carry out comprehensive health monitoring, hold training in radiation protection for workers, add radiation protection equipment, procure a surveymeter and complete records of the implementation of activities at the radiology installation. Keywords : Safety, X-Ray Radiation, Radiology, Hospital